Thiol-ene Enabled Chemical Synthesis of Truncated S-Lipidated Teixobactin Analogs - Yim, Victor V.; Cameron, Alan J.; Kavianinia, Iman; Harris, Paul W. R.; Brimble, Margaret A. (Frontiers in Chemistry, 2020)
Herein is described the introduction of lipid moieties onto a simplified teixobactin pharmacophore using a modified Cysteine Lipidation on a Peptide or Amino acid (CLipPA) technique, whereby cysteine was substituted for 3-mercaptopropionic acid (3-MPA). A truncated teixobactin analogue was prepared with the requisite thiol handle, thus enabling an array of vinyl esters to be conveniently conjugated onto the simplified teixobactin pharmacophore to yield S-lipidated cyclic lipopeptides.